The Use of Javanese by Society of Keraton Surakarta Hadiningrat - Susylowati, Eka (Journal of English Teaching and Learning Issues, 2019)
This research aims to find out Javanese form and its relationship between locutor and interlocutor. This research is qualitative in nature. The location of this research is in the Surakarta Hadiningrat palace. The language variation used in this research is daily activity and official palace ceremonies. The data are derived from the verbal interaction among society of kraton in formal and informal situation. The data were collected by recording, observing, interviewing technique. The analysis data used Hymes, ethnography method communication. The result of the research shows that the Javanese forms consists of ngoko, madya, krama, krama inggil, kedhaton and even Indonesian. Related to the relation between locator and interlocutor, the form of Javanese affected by the horizontal and vertical relation accordance with social status in the palace. The pattern of using ngoko, madya, krama has changed, moreover when Indonesian has been their repertoire.